Utilization of Big Data for SWOT Analysis in Improving Business Sustainability of MSMEs - H, Herlina (PT.KARYA GEMAH RIPAH, 2024)
SWOT analysis has become an essential method in assessing company risks, particularly in coffee shop micro, small, and medium enterprises (MSMEs), in the current digital age. This study facilitates the identification of current strengths, weaknesses, opportunities, and threats, hence empowering MSMEs to effectively address potential risks through suitable strategies. This study employs qualitative methodologies in conjunction with the utilisation of big data to get more profound understandings of company operations and market trends that impact micro, small, and medium enterprises (MSMEs). By conducting interviews and directly observing the owners and management of UMKM Cava Brew, as well as analysing large data such as online customer reviews, consumer behaviour, and transactional data. The SWOT analysis, enhanced with big data, has led to the recommendation of adaptive tactics for Cava Brew. The ideas entail including sitting amenities and expanding the range of payment options, including the integration of digital payment systems like digital wallets and QRIS, to attract a broader customer base. These measures are anticipated to enhance customer happiness and bolster Cava Brew Kopi's competitive standing in the coffee shop MSME industry.